Interior Architecture : Drafting and Perspective - Jones, Frederic H. (Frederic Hicks) (California : William Kaufmann, 1986)
A single, convenient reference that includes both the basics of drafting and examples of uniform interior design standards.
Includes bibliographical references (pages 234 - 235 )
Keywords: Architectural drawing -- Technique; Interior architecture -- Designs and plans; Architectural rendering